SPESIASI DAN BIOAVAILABILITAS LOGAM Cu DAN Zn DALAM PERAIRAN DAN SEDIMEN MUARA SUNGAI BADUNG PADA JALUR TAMAN HUTAN RAYA NGURAH RAI DENPASAR BALI - Puspasari, Dewa Ayu; Eka Suprihatin, Iryanti; Kunti Sri Panca Dewi, I G. A. (Jurnal Kimia (Journal of Chemistry); Vol. 8, No. 2 Juli 2014DO - 10.24843/JCHEM.2014.v08.i02.p02, 2014)
Metal concentration in water enviroment and sediment cannot give sufficient information about bioavailability of those metals in the waterworks. The aims of this study are to determine the bioavailability and specification of Cu and Zn in water enviroment and sediment in the estuary of Badung river in the “Taman Hutan Raya Ngurah Rai” Denpasar, Bali area. Determination of bioavailability and speciation of those metals were accomplished  by  sequencial extraction method. The results of this study show that total concentrations of  Cu, and Zn in the water samples are 0,1792 mg/L, and 0,0647 mg/L. The sum of the fraction of non-resistant and resistant fractions of Cu and Zn in the sediment obtained in this study indicates the total concentration of metals in the sediment, i.e 33,9036 mg / kg and 50,8296 mg/kg. Results of the metal speciation are as follow: fraction of Cu is dominated by resistant fraction that is 64,38 %, whereas non-resistant fractions are: 3,70 % for acid reducible and 31,89% for oxidisable organic.  Fraction of Zn is dominated by acid reducible fraction of 39,27 %, followed by organic oxidisable of 25,46 % and EFLE fraction of 1,80%, whereas the resistant fraction is 33,47 %. The percentages of Cu and Zn bioavailabilities respectively are 35,59 % ; and 66,53 %.
Keywords: Speciation, bioavailability, Cu, Zn, water, sediment